Synthesis of 2‐Acetamido‐1, 3, 4‐Tri‐O‐Acetyl‐2‐Deoxy‐D‐Mannopyranose ‐6‐Phosphate Prodrugs as Potential Therapeutic Agents. Issue 8 (17th August 2022) - Pertusati, Fabrizio; Morewood, James
Abstract: Sugar phosphates are emerging as potential therapeutic candidates for certain diseases. However, their high polarity makes them poorly absorbed by the body and their penetration inside the cell is even more difficult without a proper transporter. Amino sugar phosphates (n‐amino‐n‐deoxy‐sugars, carbohydrates in which a hydroxyl group has been replaced with an amine group), such as N ‐acetyl‐D ‐mannosamine (ManNac)‐6‐phosphate have shown potential as a treatment for a muscular disease called GNE myopathy caused by a deficiency in the production of sialic acid. However, its high polarity leads to poor absorption and consequent high dosage in humans, causing unwanted side effects. Herein, we describe the application of phosphoramidate prodrug chemistry to 1, 3, 4‐O‐acetylated N ‐acetylmannosamine (Ac3ManNAc) to deliver ManNAc‐6‐phosphate (ManNAc‐6‐P), a critical intermediate in sialic acid biosynthesis. Sialic acid deficiency is a hallmark of GNE myopathy, a rare congenital disorder of glycosylation (CDG), caused by mutations in the gene "GNE, " that limit the production of ManNAc‐6‐P. Synthetic methods were developed to provide a library of Ac3ManNAc‐6‐phosphoramidates that were evaluated in a series of studies for their potential as a treatment for GNE myopathy. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of 2‐Acetamido‐1, 3, 4‐tri‐O‐acetyl‐2‐deoxy‐D ‐mannopyranose. Basic Protocol 2 : Preparation of 3‐acetamido‐6‐((((((S)‐1‐ethoxy‐4‐methyl‐1‐oxo‐pentan‐2‐yl) amino) (phenoxy)phosphoryl) oxy) methyl) tetrahydro‐2H‐pyran‐2, 4, 5‐triyl triacetate (5). Support Protocol : Preparation of ethyl (chloro(phenoxy)phosphoryl)‐l‐leucinate.